Gender dependent accumulation of dioxins in smokers. Issue 1 (21st December 2004) - Fierens, S; Eppe, G; De Pauw, E; Bernard, A
Abstract : Aims: To evaluate the contribution of tobacco smoking to dioxin accumulation. Methods: Dioxin (17 PCDD/F) concentrations in fasting blood from 251 subjects (161 never smokers, 54 past smokers, and 36 current smokers) were quantified. Results: Whereas serum dioxin concentrations of male smokers were on average 40% higher than those of non-smokers, in women, smoking was associated with significantly lower serum dioxin levels. A synergistic potentiation of dioxin metabolism by tobacco smoke in women is postulated to explain these paradoxical findings. Conclusions: Current smoking is associated with gender dependent effects on dioxin body burden and is a potential source of confounding in human studies using blood dioxins as indicators of exposure.